Aloplastika u intrakapsulárních zlomenin krčku femuru - Skála-Rosenbaum, Jiří; Čech, Oldřich; Džupa, Valér (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2012)
The authors discuss arguments concerning indications and selection of implants and operative techniques for arthroplasty in the treatment of femoral neck fractures. Their analysis is based on long-term experience with surgical treatment of patients with hip fractures and on the evaluation of a large number of publications by well-known specialists. The assessed group included 4795 patients treated at their institution between 1997 and 2010, of whom 1532 underwent hip replacement, with 1032 receiving hemiarthroplasty (HA) and 500 having total hip replacement (THR) indicated for femoral neck fractures. A painful hemiarthroplasty due to acetabular cartilage erosion and subsequent head protrusion is still a challenging clinical problem. The most important factor in prevention of this complication remains strict adherence to indication criteria. A metal monoblock hemiarthroplasty should be indicated only in very old patients with serious co-morbidities or in patients whose pre-operative mobility has been greatly restricted. For the other cases, a modular prosthesis is preferred because it allows for more exact alignment and, if necessary, its conversion to a total hip prosthesis is relatively easy. The stem to be implanted should be the one used in standard THR procedures. A ceramic modular head then enables hemiarthroplasty to function for long with a low risk of cartilage erosion and head protrusion. Even if the choice of an optimal prosthesis, in terms of its biomechanical and biological properties, has been correct, the prosthesis' long life span and good functioning still depends on the surgeon's adherence to the principles of the correct operative technique (the head centre situated 1 to 2 mm below the level of the apex of the greater trochanter, 12- to 15-degree anteversion, articular capsule suture, and re-insertion of external rotator tendons if the Koch-Langenbeck approach is used. This is the only way of minimising acetabular erosion and other complications. Indications for total replacement include, in addition to fractures at joints affected by arthritis, most often a displaced fracture of the femoral neck found in younger patients still in good general health with a good prospect for a long life. Even if dislocation and loosening occur in these patients more often than in those with a THR procedure indicated for other reasons (primary or post-dysplastic arthritis), this therapy offers fewer complications and longer functioning in comparison with other methods of treating femoral neck fractures. A cemented prosthesis can be regarded as the standard implant; however, if the proximal femur shows good quality cortical bone, an uncemented implant can be used without a greater risk of future loosening. In the absence of hip arthritis which leads to the development of subchondral sclerosis required for the correct acetabular cup fixation, a hybrid THR with an expansion cup or a screw-in cup is recommended.
Keywords: Fracture Fixation, Internal; Humans; cementování; Cementation; Arthroplasty, Replacement, Hip; Aged; náhrada kyčelního kloubu; věkové faktory; výsledek terapie; Femoral Neck Fractures; senioři; lidé; Prosthesis Design; časové faktory; Hip Prosthesis; vnitřní fixace fraktury; Postoperative Complications; pooperační komplikace; fraktury krčku femuru; Treatment Outcome; kyčelní protézy; Age Factors; protézy - design; Time Factors